PERAN PARA SULTAN DALAM PENYEBARAN ISLAM DI GORONTALO - Sirajuddin Sirajuddin (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This study aims to describe the role of royales in Former GorontaloKingdoms. This study was conducted in Gorontalo. Data was collectedusing interview and observation. Interview was conducted with localIslamic Historician.This Study Indicates that Islamic come into Gorontalo in several ways,such are marriage, education, and politic. The role of Former GorontaloRoyales was very important to Islamic diaspora in Gorontalo society.The Kings that have main role are Sultan Amai, Sultan Matolodulakiki,and Sultan Jogugu Eyato. The kings succesed to integrate Islamic valueinto local tradition